Coconut Shell Liquid Smoke Promotes Burn Wound Healing - Vita Murniati Tarawan MD, PhD; Kemala Isnainiasih Mantilidewi MD, PhD; Ika Miqra Dhini MD, MHS; Putri Teesa Radhiyanti MD, MHS; Endang Sutedja MD, PhD (SAGE Publishing, 2017)
The aim of this study was to evaluate burn wound healing activity of coconut shell liquid smoke (CS-LS) in a burn wound animal model. Burn wound-induced mice were treated with CS-LS (CS-LS group), povidone iodine 10% (povidone group), or NaCl 0.9% (NaCl group). Application of CS-LS promoted wound contraction compared to that of the povidone and NaCl groups ( P < .05). This study showed a positive correlation between the number of fibroblasts and wound contraction. The number of fibroblasts was highest in the CS-LS group, compared to that of the povidone and NaCl groups ( P < .05). In conclusion, CS-LS promotes burn wound healing by one possible mechanism, by increasing the number of fibroblasts. The results indicate that further experimental trials are needed to develop CS-LS as an alternative topical drug for burn wound healing.